INNV-03. DEVELOPMENT OF A NOVEL DUAL-MODALITY BALLOON IMPLANT FOR SIMULTANEOUS HIGH-DOSE-RATE BRACHYTHERAPY AND MAGNETIC NANOPARTICLE HYPERTHERMIA OF BRAIN TUMOR RESECTION CAVITIES. (12th November 2021) - Wan, Shuying; Rodrigues, Dario; Stauffer, Paul; Kwiatkowski, Janet; Khanna, Omaditya; Judy, Kevin; Yu, Yan; Shi, Wenyin; Hurwitz, Mark
Abstract: PURPOSE: To develop a novel thermobrachytherapy (TBT) balloon implant that delivers hyperthermia and radiation simultaneously, with three specific aims: 1) to fabricate a prototype TBT balloon device; 2) to verify compatibility of all heating and radiation delivery components and evaluate heat and radiation dosimetry in full size skull/brain phantom models; and 3) to characterize in vivo heating patterns in pig brain. METHODS: Five 3cm diameter TBT balloons were fabricated. Each balloon has two layers: an inner layer to be filled with saline to expand the resection cavity, and an outer layer to be filled with magnetic nanoparticle (MNP) solution to absorb energy from an external magnetic field hence generate heat. The balloon shaft houses 4 ports to fill inner and outer layers, insert a high-dose-rate brachytherapy source into the balloon center, and a fiber optic sensor into the outer layer to monitor and control balloon temperature. A 3D-printed skull phantom was filled with brain tissue-equivalent gel for in-phantom measurements of heating around a TBT balloon. Optically stimulated luminescent dosimeters and Gafchromic film were used to measure radiation dose; while motorized temperature probes placed in catheters were inserted in surrounding gel for thermal mapping. For in vivo experiments, a 1cm balloon was specifically fabricated for pigs 40-50 kg. RESULTS: The presence of MNP, magnetic field, and 43-55°C heating did not affect radiation dose significantly. Thermal mapping demonstrated spherically symmetric heating in both phantom and in vivo brain tissue, where a higher concentration of MNP and stronger magnetic field of 1.6-4.5 kA/m at 133 kHz was used to achieve temperatures of 55°C in the much smaller balloon. CONCLUSION: Novel dual-modality balloons have been fabricated and tested successfully in the lab and i n vivo, hence providing crucial information to validate thermal modeling for combined heat and radiation treatment of brain tumor resection cavities.